Global Strong Solution to the 3D Incompressible Navier-Stokes Equations with General Initial Data (Journal of Mathematical Study, 2015)
We study the existence of global strong solution to an initial-boundary value(or initial value) problem for the 3D nonhomogeneous incompressible Navier-Stokesequations. In this study, the initial density is suitably small (or the viscosity coefficientsuitably large) and the initial vacuum is allowed. Results show that the unique solutionof the Navier-Stokes equations can be found.
Keywords: Incompressible Navier-Stokes equations; strong solutions; vacuum.